2020
DOI: 10.1002/ange.201913243
|View full text |Cite|
|
Sign up to set email alerts
|

An Organic–Inorganic Hybrid Cathode Based on S–Se Dynamic Covalent Bonds

Abstract: A diphenyl trisulfide–selenium nanowire (DPTS‐Se) organic–inorganic hybrid cathode material is presented for rechargeable lithium batteries. During discharge, three voltage plateaus associated with three lithiation processes are observed. During recharge, the combination of the radicals formed upon delithiation leads to several new phenyl sulfoselenide compounds which are confirmed by HPLC‐QTof‐MS. The hybrid cathode exhibits superior cycling stability over pristine Se or DPTS as cathode alone. The first disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Recently, our group reported a diphenyl trisulfide (Ph‐S 3 ‐Ph)‐Se nanowire (DPTS‐Se) hybrid cathode based on S−Se dynamic covalent bonds for Li batteries . This is the first time an organic polysulfide was combined with an inorganic Se electrode.…”
Section: Hybrid Materials Containing S−se Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our group reported a diphenyl trisulfide (Ph‐S 3 ‐Ph)‐Se nanowire (DPTS‐Se) hybrid cathode based on S−Se dynamic covalent bonds for Li batteries . This is the first time an organic polysulfide was combined with an inorganic Se electrode.…”
Section: Hybrid Materials Containing S−se Bondsmentioning
confidence: 99%
“…Reprinted with permission from refs. and . Copyright 2020, Wiley‐VCH, Weinheim, and copyright 2019, Nature Publishing Group, respectively.…”
Section: Hybrid Materials Containing S−se Bondsmentioning
confidence: 99%
“…[15] More recently, polymers containing multiple SÀ S bonds that have been synthesized through inverse vulcanization, [16] incorporation of covalent frameworks, [17] and condensation reactions have been demonstrated. [18] In addition to polymers, linear compounds, cyclics, [6c] hybrids, [19] and compounds with unique functional groups have been employed as cathode materials. [20] Previous reports have demonstrated that the organosulfur compounds can decently mitigate the shuttle effect in Li-S batteries.…”
Section: Introductionmentioning
confidence: 99%